Understanding cross-border mergers and acquisitions of African firms: The role of dynamic capabilities in enabling competitiveness amidst contextual constraints - William Y. Degbey; Taina Eriksson; Peter Rodgers; Nnamdi Oguji (Wiley, 2022)
This article builds on existing international business literature that examines the drivers of cross-border mergers and acquisitions (M&As) within emerging and developing economy contexts, theoretically exploring how dynamic capabilities (DCs) are connected to these drivers, and how African emerging multinational enterprises (EMNEs) can pursue them to achieve competitiveness. The article's contribution is the development of a DC framework and testable propositions for African EMNEs' cross-border M&As. The theoretical framework shows the division of DC dimensions-sensing, seizing, and transforming-and establishes explanations for their linkage with institutional and resource drivers for African EMNEs' cross-border M&A competitiveness. In addition, the article outlines managerial implications to this effect. Overall, the article contributes to the emerging literature on the international expansion of African EMNEs through cross-border M&As by underscoring the role of DCs.